Meningkatkan Kreativitas Anak melalui Metode Bermain dengan Menggunakan Media Plastisin - Ni Komang Ayu Sri Lestari; Selfina Wallu; Priska Benedikta Jenahat; Gaudensiana Delsi (Early Childhood Education Development and Studies (ECEDS), 2021)
The purpose of this class action research is to increase the creativity of group B children at the Pembina State Kindergarten, Dawan District. The research subjects were the children of Group B of Pembina State Kindergarten, Dawan District, which consisted of 15 children. This research was conducted in 2 cycles, namely cycle I and cycle II. The data collection technique used is observation in the form of observation sheets, documentation, works. The data analysis method used is descriptive analysis with a qualitative approach. Based on the results of the discussion that has been described previously, it can be concluded that playing plasticine from clay can increase creativity in students. This can be seen in the increase in frequency and percentage that occurred in the initial condition of 15 children, only 3 people got a score of 2 (20%), in cycle I it increased to 6 people got a score of 2 (40%) and 9 people got a score of 3 (60%) then in cycle II it increased again to 12 students got a score of 3 and a score of 4 (80%).